Anticipated emotions of significant others as social influence: Can they predict students’ smoking abstinence continuance intention? - Simamora Bilson (Jurnal Ekonomi Perusahaan, 2021)
In the Theory of Planned Behavior (Ajzen, 1991), subjective norms (SN) represent social influence on an individual's behavior. This famous model of behavior postulates that an individual is under pressure or expectation of significant others to perform or not to perform a behavior. This study starts from the premise that an individual can take the initiative and regulate his or her behavior to generate anticipated emotion of significant others’ (AESO). The question is, can the AESO function as the SN to represent the social factor in influencing students' smoking abstinence continuance intention? To answer this question, the author conducts the study upon 235 non-smoker students. The result is; first, negative AESO can carry out that function. However, positive AESO and SN fail to do so. Therefore, besides the SN, as shown by this study, the AESO, represented by negative AESO, can be regarded as a social influence component of an individual's behavioral intention. Other researchers are encouraged to validate this finding in different contexts of behavior.